Digital human models. (28th January 2015) - Smith, Gregory C.; Smith, Shana S.
This study describes digital human models. This study also describes trends in digital human models, shows that the most important trend in digital human models is integrated digital human models, shows that integrated digital human models are frameworks and models and describes frameworks and models that can be used to create digital human models. The results can be used to describe, select, or create digital human models.